Cartographier l’incartographiable ? Retour sur la mise en place d’une cartographie collaborative institutionnelle pour la végétalisation urbaine participative à paris - Carolina Mudan Marelli; Ornella Zaza (Netcom)
Based on a double ethnographic survey within Paris City Hall and with inhabitants, this contribution focuses on the process of setting up a digital platform to support participatory urban greening process in Paris. Faced with the richness of the practices, imaginaries and interactions that characterize inhabitants practices of greening, the online cartographic representation shows, on the one hand, a flattening of the reality on the ground, induced by the dominant logics of quantification and cataloguing, and on the other hand, distorts the Parisian narrative about urban nature, which is built around figures that dialogue more in an international than in a local political arena. This online collaborative mapping seems to be mostly a tool for political communication, which doesn’t really contribute to the emergence of new collaborative processes of urban management or planning with inhabitants.